Artistic creativity and dementia. A study of assessment by experts - H. Belver, Manuel; Ullán, Ana Mª (Arte, Individuo y Sociedad, 2017)
The goal of this study was to determine whether experts attribute a series of images created by people with dementia who were participating in a program of contemporary art education to artists or to people without prior artistic experience. In this way, we sought to obtain an indicator of the artistic quality of the images produced by people with dementia. Participants were 122 specialists in art to whom were presented 30 images, 15 works by professional artists and 15 created by people with dementia. For each of the 15 images created by the people with dementia, we calculated the proportion of experts who attributed the image to a professional artist. The results indicated that, in a significant number of cases, which varied according to the images, the experts attributed the images to professional artists. The judgment of the experts reinforcing the idea of the creative potential of people with dementia.